Scope of Practice of Midwifery within the Nursing Profession: Perception of Midwifery Trained Registered Nurses, a Qualitative Study - Jayathilake, M.R.S.; Samarasinghe, K.; Perera, P.P.R.; Jayasuriya, M.V.F.; Molligoda, H.D. (University of Sri Jayewardenepura, Nugegoda, 2015)
Objectives: Midwifery scope of practice within the nursing profession has been a contentious issue in South Asian settings. To address a knowledge gap in Sri Lanka, we explored Midwifery Trained Registered Nurses' (MTRNs) perceptions of their role in intra-natal and post-natal units in Tertiary care hospitals in Western province of Sri Lanka. Methods: Three focus group discussions (FGDs) were conducted with 22 MTRNs from selected hospitals. FGDs were recorded, transcribed verbatim, and analyzed using qualitative content analysis. Results: Three emerging themes were identified: role of MTRN, role of other professionals and role disagreements. MTRNs described 'my role' in terms of individual tasks, placing themselves outside of the arena of the others in the team. Their role was characterized by observation of their own seniors and peers. 'Others' including midwives and medical officers, who were identified outside of the realm of their group, performed tasks and held responsibilities which constantly overlapped with their own. Disagreements with regards to their roles and responsibilities were common between MTRN and others, resulting in confusion, frustrations and conflicts. Labour room was the most contentious setting where lack of clear role identification created conditions for conflict. Conclusions: MTRN's practice was circumstance driven and limited in scope. Different professional groups lacked clarity regarding their own roles and responsibilities and as a result, failed to develop a team identity. Clear job descriptions, written protocols and delegation of responsibilities should define MTRN's scope of practice in order to improve the dynamics within maternity healthcare team.